2016
DOI: 10.1180/claymin.2016.051.3.06
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acid activation and calcination of halloysite on the efficiency and selectivity of Pb(II), Cd(II), Zn(II) and As(V) uptake

Abstract: The present study investigated the efficiency and mechanisms of aqueous Pb(II), Cd(II), Zn(II) and As(V) adsorption on natural (H), calcined (HC), and acid-activated halloysite (HA). The XRD and FTIR measurements indicated that the aluminosilicate framework was not affected by high-temperature treatment, in contrast to acid activation, which led to structural changes mainly in the tetrahedral sheet. The sorption of cations on H sample was low, though it was most effective for As(V). The X-ray photoelectron spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 46 publications
2
9
0
1
Order By: Relevance
“…8). These result were in agreement with previously reported studies (Maziarz, Matusik 2016). After coating the halloysite surface with Fe 3 O 4 and applying heat treatment, the desorption decreased.…”
Section: Desorption Experiments Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…8). These result were in agreement with previously reported studies (Maziarz, Matusik 2016). After coating the halloysite surface with Fe 3 O 4 and applying heat treatment, the desorption decreased.…”
Section: Desorption Experiments Resultssupporting
confidence: 94%
“…Literature on Cd(II) and Pb(II) ionic species distribution versus pH reports that the dominant forms at pH < 6.0 are Cd 2+ and Pb 2+ , Pb(OH) + , respectively which is strictly connected with the metals' hydrolysis constants (Smičiklas et al 2000;Xu et al 2008). Previous studies indicated that the adsorption of Cd(II) by the H sample occurs mainly through ion exchange, while in the case of Pb(II) removal both ion exchange and surface complexation can take place (Matusik 2016;Maziarz, Matusik 2016). This may be evidence for lower adsorption in the case of Cd(II).…”
Section: The Mechanisms and Factors Influencing Adsorptionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar observations were made for Zn 2+ where the average velocity decreased to ≈133 µm (Figure B). The decrease in the velocities of nanomotors in the presence of Zn 2+ and Cd 2+ can be attributed to the adsorption of heavy metals onto the Halloysite nanoclay surface . The ions get attached onto the active sites of the Halloysite nanoclay which subsequently blocks the platinum layer on the outer surface of the nanoclay.…”
Section: Resultsmentioning
confidence: 99%
“…The HNTs find several applications such as ceramic, support for catalysts and other functional materials [27,28]. Recently, raw halloysite was successfully tested as adsorbents for removal of dyes, heavy metals and pollutants from aqueous solutions [e.g., [29][30][31].…”
Section: Introductionmentioning
confidence: 99%